+0

# solve for x

0
332
3
+314

1/5(x+15)=1/2-1/3(x-7)

ISmellGood  Aug 22, 2017
Sort:

#1
0

Solve for x:
(x + 15)/5 = (7 - x)/3 + 1/2

Put each term in (7 - x)/3 + 1/2 over the common denominator 6: (7 - x)/3 + 1/2 = 3/6 + (2 (7 - x))/6:
(x + 15)/5 = 3/6 + (2 (7 - x))/6

3/6 + (2 (7 - x))/6 = (2 (7 - x) + 3)/6:
(x + 15)/5 = (2 (7 - x) + 3)/6

2 (7 - x) = 14 - 2 x:
(x + 15)/5 = (14 - 2 x + 3)/6

Add like terms. 3 + 14 = 17:
(x + 15)/5 = (17 - 2 x)/6

Multiply both sides by 30:
6 (x + 15) = (30 (17 - 2 x))/6

30/5 = (5×6)/5 = 6:
6 (x + 15) = (30 (17 - 2 x))/6

30/6 = (6×5)/6 = 5:
6 (x + 15) = 5 (17 - 2 x)

Expand out terms of the left hand side:
6 x + 90 = 5 (17 - 2 x)

Expand out terms of the right hand side:
6 x + 90 = 85 - 10 x

Add 10 x to both sides:
10 x + 6 x + 90 = (10 x - 10 x) + 85
16 x + 90 = 85

Subtract 90 from both sides:
16 x + (90 - 90) = 85 - 90
16 x = -5

Divide both sides of 16 x = -5 by 16:
x = (-5)/16

Guest Aug 22, 2017
#2
+526
0

First, let's distribute the left side of the equation

1/5x+3=1/2-1/3(x-7)

Then let's distribute 1/3 to (x-7) on the right side

1/5x+3=1/2-1/3x-7/3

There are too many fractions...so multiply 30 to both sides. 30 is the LCM of 2, 3, and 5.

Then we get 6x+90=15-10x+70. I admit there are other ways to do it...

Add 10x to both sides to get 16x +90=15+70

Simplify to get 16x+90=85

Subtract 90 to both sides and get 16x=-5

Divide both sides by 16 and get x=-5/16

x=-5/16.

(Oh, I see someone wrote the answer while I was typing this. I'll post this anyway...)

Gh0sty15  Aug 22, 2017
#3
+19207
0

solve for x

1/5(x+15)=1/2-1/3(x-7)

$$\begin{array}{|rcll|} \hline \frac15(x+15) &=& \frac12- \frac13(x-7) \quad & | \quad \times 5 \\ \frac55(x+15) &=& \frac52- \frac53(x-7) \\ x+15 &=& \frac52- \frac53(x-7) \quad & | \quad \times 3 \\ 3(x+15) &=& \frac{5\cdot 3}{2}- \frac{5\cdot 3}3(x-7) \\ 3(x+15) &=& \frac{15}{2}- 5(x-7) \quad & | \quad \times 2 \\ 2\cdot 3(x+15) &=& \frac{15\cdot 2}{2}- 2\cdot 5(x-7) \\ 6(x+15) &=& 15- 10(x-7) \\ 6x+6\cdot 15 &=& 15- 10x -10(-7) \\ 6x+90 &=& 15- 10x +70 \quad & | \quad + 10x \\ 10x+6x+90 &=& 15 +70 \\ 16x+90 &=& 85 \quad & | \quad -90\\ 16x &=& 85 -90 \\ 16x &=& -5 \quad & | \quad : 16 \\ \mathbf{x} & \mathbf{=} & \mathbf{-\frac{5}{16}} \\ \hline \end{array}$$

heureka  Aug 23, 2017

### 30 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details